Execution by organ procurement: Breaching the dead donor rule in China. Issue 7 (4th April 2022) - Robertson, Matthew P.; Lavee, Jacob
Abstract : The dead donor rule is fundamental to transplant ethics. The rule states that organ procurement must not commence until the donor is both dead and formally pronounced so, and by the same token, that procurement of organs must not cause the death of the donor. In a separate area of medical practice, there has been intense controversy around the participation of physicians in the execution of capital prisoners. These two apparently disparate topics converge in a unique case: the intimate involvement of transplant surgeons in China in the execution of prisoners via the procurement of organs. We use computational text analysis to conduct a forensic review of 2838 papers drawn from a dataset of 124 770 Chinese‐language transplant publications. Our algorithm searched for evidence of problematic declarations of brain death during organ procurement. We find evidence in 71 of these reports, spread nationwide, that brain death could not have properly been declared. In these cases, the removal of the heart during organ procurement must have been the proximate cause of the donor's death. Because these organ donors could only have been prisoners, our findings strongly suggest that physicians in the People's Republic of China have participated in executions by organ removal. Abstract : A computational text analysis of over 2, 000 Chinese‐language medical publications finds that transplant surgeons in the People's Republic of China have participated in the execution of prisoners by procuring their organs before brain death was determined.